HUBUNGAN KECERDASAN EMOSIONAL DENGAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP NEGERI 10 KOTA JAMBI - Heidy Fitriah, Nur; Pransiska, Susy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low emotional intelligence of some students, as evidenced by their difficulty in recognizing and controlling their emotions, lack of empathy, low cooperation skills, and motivation to learn Islamic Religious Education that only focuses on academic grades. This study aims to determine the level of students' emotional intelligence, the level of learning outcomes in Islamic Religious Education, and the relationship between the two at SMP Negeri 10 Kota Jambi. This study used a quantitative approach with a correlational method, involving 115 students as samples through random sampling techniques. The research instruments were emotional intelligence questionnaires and Islamic Religious Education learning outcome tests. Data analysis included descriptive statistics, normality tests, linearity tests, Pearson correlation analysis, t-tests, and coefficient of determination (R²) tests. The results showed that the students' emotional intelligence level was in the good category (81.77%) and their Islamic Religious Education learning outcomes were also good (77.75%). Pearson's correlation analysis showed a significant and very strong relationship between emotional intelligence and learning outcomes (r = 0.854; p = 0.000 < 0.05). The coefficient of determination (R²) of 0.729 indicates that emotional intelligence contributes 72.9% to learning outcomes, while the rest is influenced by other factors. In conclusion, emotional intelligence plays an important role in improving students' Islamic Education learning outcomes.